Coronary atherosclerosis in outlier subjects at the opposite extremes of traditional risk factors: Rationale and preliminary results of the Coronary Atherosclerosis in outlier subjects: Protective and novel Individual Risk factors Evaluation (CAPIRE) study - Magnoni, Marco; Andreini, Daniele; Gorini, Marco; Moccetti, Tiziano; Modena, Maria Grazia; Canestrari, Mauro; Berti, Sergio; Casolo, Giancarlo; Gabrielli, Domenico; Marraccini, Paolo; Pontone, Gianluca; Masson, Serge; et al. (The American heart journal, 2016)
Although it is generally accepted that cardiac ischemic events develop when coronary atherosclerosis (coronary artery disease [CAD]) has reached a critical threshold, this is true only to a first approximation. Indeed, there are patients with severe CAD who do not develop ischemic events; conversely, at the other extreme, individuals with minimal CAD may do. Similar exceptions to this paradigm include patients with diffuse CAD with a low risk factor (RF) profile and others with multiple RFs who develop only mild or no CAD. Therefore, the CAPIRE project was designed to investigate whether the specific study of these extreme outlier populations could provide clues for identification of yet unknown risk or protective factors for CAD and ischemic events. In the CAPIRE study, 481 subjects without previous symptoms or history of ischemic heart disease and normal left ventricular systolic function undergoing coronary computed tomography angiography have been selected based on coronary computed tomography angiography findings and cardiovascular RF profile. Therefore, in the whole population, 2 extreme outlier populations have been identified: (1) subjects with no CAD despite multiple RFs, and (2) at the opposite extreme, subjects with diffuse CAD despite a low-risk profile. Each subject has been characterized by clinical, anatomical imaging variables of CAD and baseline circulating biomarkers. Blood samples were collected and stored in a biological bank for further advanced investigations. The project is designed as a prospective, observational, international multicenter study with an initial cross-sectional analysis of clinical, imaging, and biomolecular variables in the selected groups and a longitudinal 5-year follow-up.